Effect of Various Red Dragon Fruit Peel (Hylocereus polyrhizus) and Yellow Pumpkin (Cucurbita moschata) Combinations and Carrageenan Proportion on the Quality of the Jam - Suparno; Fatmawati, Devi; Fitriani, Noor Rezky; Rahman, Arief; Tarigan, Siska Melani Br; Faridawaty, Evi; Sadono, Agus; Gunawan, William Ben; A, Yan Nurrezkytaku; Dewi, Reza Sukma; Kumalawati, Dian Aruni; Sanjaya, Aldy Rahman Dharma Putra (Nutrición Clínica y Dietética Hospitalaria, 2023)
Objective: the objective of this study was to analyze the thickening effect of different red dragon fruit peel, yellow pumkin, and carrageenan proportions on the jam quality whitch is rich in starch and antioxidans and liked by costumer. Material and methods: A Descriptive and diagnostic analyzed of proportion and quality of the jam with different composition of red dragon fruit peel, yellow pumpkin, and carrageenan. The result material process is tested with physicochemical and organoleptic. Result: The treatment E is the best treatment, as evidenced by the water content of 24.46 ± 1,62%, ash content of 2.47 ± 0,04%, 32.75 ± 2,09% reducing sugar content, crude fiber of 5.67 ± 0,59%, antioxidant activity of 32,49 ± 0.28 ppm, and organoleptic score of 4.29± 0,52 (pink) and 4.05± 0.26 (liked) for color and taste, respectively. Conclusion: The quality of jam based on the physicochemical and organoleptic properties preferred by the panelists is formula E with 50% red dragon fruit skin, 50% yellow pumpkin, and a carrageenan concentration of 0.60%.